Influence of chlorpromazine on the resistance of erythrocytes of rats of different ages to hypertonic conditions - Koba, L.; Shapkina, O.; Zhuikova, A.; Bondarenko, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The osmotic stability of native and modified with chlopromazine (CPR) erythrocytes of 1- and 12-month rats to hypertonic conditions in sucrose solutions and hypertonic shock (4.0 M NaCl) has been studied. It has been shown that 2-min incubation of rat erythrocytes of different ages in hypertonic sucrose media does not reveal any differences in the osmotic stability of these cells. In this case, CPR does not affect cell hemolysis. An increase of the incubation time in hypertonic sucrose solutions to 30 minutes allowed detecting a greater osmotic sensitivity of erythrocytes of 1-month animals to the action. In this case, the protective effect of CPR for older age rat erythrocytes (12 months) has been established. It has been found that in 4.0 M NaCl the hemolysis level of animal erythrocytes of both age groups increases with preliminary incubation (2 min) in a sucrose medium with a concentration of 0.7 M and above. With increasing exposure time (30 min) in sucrose hypertonic solutions, the sensibilization of animal erythrocytes of both age groups to the action of hypertonic shock is also intensified. In this study it has been shown that the influence of CPR on the sensitivity of 1-month-old animal erythrocytes to the transfer in 4.0 M NaCl depends on the tonicity and duration of the cell initial incubation in sucrose solutions. Thus, CPR increases the osmotic resistance of erythrocytes, which were preexposed in sucrose solutions at a concentration of 0.6–0.8 M for 2 and 30 min. Some increase of hemolysis level of these animals erythrocytes modified with CPR in 4.0 M NaCl has been observed after 2 min of incubation in sucrose solutions at a concentration of 0.27–0.5 M. The exclusively protective influence of CPR on 12-month-old animal erythrocytes in conditions of hypertonic shock has been revealed. A quantitative estimation of the efficiency of CPR at hypertonic shock (4.0 M NaCl) of different age animal erythrocytes has been carried out by calculation of the antihemolytic activity value (AG). Short-term incubation (2 min) in a sucrose media does not reveal any differences in the values of AG of CPR for erythrocytes of both age groups. For the cells of young rats, increase of AG of CPR is observed at incubation in sucrose medium to 30 min and for erythrocytes of the older group – to 10 min. With an increase in incubation time of up to 60 min the CPR efficiency in hypertonic saline media is reduced for rat cells in both age groups but in varying degrees.